Transdermal permeation of inorganic cerium salts in intact human skin. (August 2022) - Magnano, Greta Camilla; Marussi, Giovanna; Larese Filon, Francesca; Crosera, Matteo; Bovenzi, Massimo; Adami, Gianpiero
Abstract: The stratum corneum protects the body against external agents, such as metals, chemicals, and toxics. Although it is considered poorly permeable to them, comprising the major barrier to the permeation of such substances, it may become a relevant gate of entry for such molecules. Cerium (Ce) is a lanthanide that is widely used in catalytic, energy, biological and medicinal applications, owing to its intrinsic structural and unique redox properties. Cerium salts used to produce cerium oxide (CeO2 ) nanostructures can potentially come into contact with the skin and be absorbed following dermal exposure. The objective of this study was to investigate the percutaneous absorption of three inorganic Ce salts: cerium (III) chloride (CeCl3 ); cerium (III) nitrate (Ce(NO3 )3 ) and ammonium cerium (IV) nitrate (Ce(NH4 )2 (NO3 )6 ), which are commonly adopted for the synthesis of CeO2 using in vitro - ex vivo technique in Franz diffusion cells. The present work shows that Ce salts cannot permeate intact human skin, but they can penetrate significantly in the epidermis (up to 0.29 μg/cm 2 ) and, to a lesser extent in dermis (up to 0.11 μg/cm 2 ). Further studies are required to evaluate the potential effects of long-term exposure to Ce. Graphical abstract: Unlabelled Image Highlights: Skin may be an entry route of xenobiotics inducing local effects. Human skin permeation of inorganic Cerium (Ce) salts was negligible. No potential risk of Ce to reach the systemic circulation.